2013
DOI: 10.19106/jmedscie004504201301
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between sirtuin 1 (SIRT1) expression and tumor size, Proliferating Cell Nuclear Antigen (PCNA) expression and histological grading in rat breast carcinoma induced by dimethylbenz( α )anthracene (DMBA)

Abstract: Controversy regarding the role of SIRT1 in pathology of cancers exists and is still under debate. SIRT1 could act as either a tumor supressor or tumor promotor. This study was conducted to evaluate the relationship between SIRT1 expression and tumor size, Proliferating Cell Nuclear Antigen (PCNA) expression and histological grading in rat breast carcinoma induced by dimethylbenz(á)anthracene (DMBA). Thirty female Sprague Dawley rats were randomly allocated into three groups with 10 rats in each group. Group 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…17 This is consistent with tumorigenesis process, that proved with nodules formation in DMBAinduced Sprague Dawley. 12,18 Similar results were obtained by Padauleng et al, 18 which discovered that SIRT1 expression on DMBAinduced rat was higher than the un-induced ones. Furthermore, Padauleng et al, 18 found that SIRT1 expression was observed in poor histological grade carcinoma SD rats and there was a positive correlation between size of the nodules and PCNA proliferation marker with SIRT1 expression.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…17 This is consistent with tumorigenesis process, that proved with nodules formation in DMBAinduced Sprague Dawley. 12,18 Similar results were obtained by Padauleng et al, 18 which discovered that SIRT1 expression on DMBAinduced rat was higher than the un-induced ones. Furthermore, Padauleng et al, 18 found that SIRT1 expression was observed in poor histological grade carcinoma SD rats and there was a positive correlation between size of the nodules and PCNA proliferation marker with SIRT1 expression.…”
Section: Discussionsupporting
confidence: 59%
“…In addition, DMBA-induced rats had positive breast carcinoma, characterized by the formation of nodules. 12,18 It proves that NF-κB expression is high in SD rats with breast tumors. These results are consistent with study conducted by Rahman et al, 23 who reported that presentation of NF-κB expression in DMBA-induced rats is higher than control group rat (corn oil-only).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation